Aspects of the Complement System in New Era of Xenotransplantation - Miyagawa, Shuji; Maeda, Akira; Toyama, Chiyoshi; Kogata, Shuhei; Okamatsu, Chizu; Yamamoto, Riho; Masahata, Kazunori; Kamiyama, Masafumi; Eguchi, Hiroshi; Watanabe, Masahito; Nagashima, Hiroshi; Ikawa, Masahito; et al. (Frontiers in Immunology, 2022)
After producing triple (Gal, H-D and Sda)-KO pigs, hyperacute rejection appeared to no longer be a problem. However, the origin of xeno-rejection continues to be a controversial topic, including small amounts of antibodies and subsequent activation of the graft endothelium, the complement recognition system and the coagulation systems. The complement is activated via the classical pathway by non-Gal/H-D/Sda antigens and by ischemia-reperfusion injury (IRI), via the alternative pathway, especially on islets, and via the lectin pathway. The complement system therefore is still an important recognition and effector mechanism in xeno-rejection. All complement regulatory proteins (CRPs) regulate complement activation in different manners. Therefore, to effectively protect xenografts against xeno-rejection, it would appear reasonable to employ not only one but several CRPs including anti-complement drugs. The further assessment of antigens continues to be an important issue in the area of clinical xenotransplantation. The above conclusions suggest that the expression of sufficient levels of human CRPs on Triple-KO grafts is necessary. Moreover, multilateral inhibition on local complement activation in the graft, together with the control of signals between macrophages and lymphocytes is required.